Business Process Change through Trusted Third Party Repository (TTPR): A Case Study of the CeDA in Korea - Cho, Namdo (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study introduces new model of digital repositories called Trusted Third Party Repository (TTPR) in Korea, its service offerings and business impacts. As a government approved institution, TTPR offers third party archiving service, creates and verifies certificates for the retained e-documents, and plays a role as a trusted intermediary of e-documents exchange. Cette étude propose un nouveau modèle de dépôt numérique appelé Trusted Third Party Repository (TTPR) appliqué en Corée, une gamme de services et leurs impacts sur les affaires. Approuvés par le gouvernement, les TTPR sont des institutions qui offrent des services d’archivage, créent et valident des certificats pour les documents électroniques conservés et jouent un rôle en tant qu’intermédiaires de confiance garants de l’échange de documents électroniques.